“Colon”ised by the unexpected: a case of extrauterine epithelioid trophoblastic tumour - Shalini Radhakrishnan; Nischitha N. Suvarna; Saraswathy Sreeram; Srirama Bhat (Diagnostic Pathology)
Abstract Introduction Extrauterine epithelioid trophoblastic tumour is an exceedingly rare and aggressive form of gestational trophoblastic disease that arises outside the uterus and is characterised by the proliferation of intermediate trophoblastic cells. Unlike more common forms of gestational trophoblastic diseases, such as hydatidiform moles and choriocarcinoma, this entity presents unique diagnostic and therapeutic challenges due to its atypical location and clinical features. Thus far, no documented cases of this entity have been reported in the colon. Case presentation We report the case of a 42-year-old woman who presented with complaints of lower abdominal pain and a palpable mass in the left iliac fossa, initially suspected to be an ectopic pregnancy. On radiological evaluation, a provisional diagnosis of gastrointestinal stromal tumour was made, following which the patient underwent a left colectomy with resection and anastomosis, and the excised specimen on comprehensive histopathological and immunohistochemical analysis was diagnosed as a case of extrauterine epithelioid trophoblastic tumour. However, the patient’s condition deteriorated, and she succumbed to the disease one month after the diagnosis. Conclusion The rarity of extrauterine trophoblastic tumours contributes to limited clinical experience and treatment protocols, resulting in poor prognoses. This case report highlights the importance of histopathological examination for a confirmatory diagnosis, ensuring timely identification and improving patient outcomes.